ECONOMIC FIGURES AND INDICATORS - Abadov Masim Kazim oglu (Research Focus International Scientific Journal, 2024)
To date, a unified coordination system has not been created for the rapid implementation of the topic of digital currency creation and other areas created by the new industrial revolution. The promotion of digital transformations in the pilot mode should be started without delay by attracting specialists with relevant professionalism in this field from every region of Azerbaijan, and as Mr. President mentioned, Azerbaijan should be a leader in this field. Because, other countries are already advancing by taking large steps in the existing field. Falling behind this trend is dangerous. There are many important issues that central banks and regulators must consider when implementing digital currencies. Each country has to find different answers and develop strategies in this matter. Implementing digital currencies is a complex process and requires careful planning. The impact of cryptocurrencies on the economy is multifaceted and has both positive and negative aspects. How cryptocurrencies will affect economies in the future depends mainly on their regulation, technological developments and how they will be accepted by the general public.